HUBUNGAN PEMBERIAN ASI EKSLUSIF DENGAN KEJADIAN STUNTING PADA BALITA DI DESA PERLIS WILAYAH KERJA PUSKESMAS TANGKAHAN DURIAN KABUPATEN LANGKAT - Rani Kawati Damanik; Erwin Silitonga; Ida Ria Royenti Sidabukke; Putri Delima Perdana (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2022)
Stunting is a condition of failure to thrive in children under five years of age due to chronic malnutrition so that children are too short of height according to WHO 2005, ie Z-Score is less than -2SD. And exclusive breastfeeding is a condition where the baby only receives breast milk from the biological mother or breastfeeding mother, expressed breast milk and no other liquid or food. The purpose of this study was to analyze the relationship between exclusive breastfeeding and stunting in children under five. This type of research is an observational analytic with a retrospective research design conducted in Perlis Village, Tangkahan Durian Health Center Work Area, Langkat Regency. The population of this study were all mothers who had children under five as many as 364 toddlers. The sample in this study was 79 children under five with purposive sampling technique. This research was conducted in February-July 2019. Data collection was carried out by measuring the height of toddlers and filling out observation sheets. Bivariate analysis using the Shapiro Wilk test with a probability value (p) value of 0.05. The results of research conducted in Perlis Village, Tangkahan Durian Public Health Center, showed that 15 children who were given exclusive breastfeeding had stunting status (19.0%) and 27 (34.2%) children who were not given exclusive breastfeeding had stunting status. = 0.001 (p>0.05) from the statistical test results, thus there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers in Perlis Village, Tangkahan Durian Health Center Work Area, Langkat Regency. This study suggests that mothers be more active in breastfeeding their babies with the support of the role of puskesmas nurses to provide education about exclusive breastfeeding. Keywords: Exclusive Breastfeeding, Stunting Incidence, Toddler